Korelasional antara Minat Belajar, Pengetahuan Awal dan Literasi Digital terhadap Motivasi Belajar Siswa - Lestari, Adinda; Hidayat, Hendra (Lembaga Yasin AlSys, 2025)
Motivation can be said as a drive owned by students, which will make them do an action and with this motivation students will be enthusiastic to follow the lesson. There are many factors that drive motivation, including interest in learning, prior knowledge and digital literacy. The purpose of this study is to measure the correlation between interest in learning, prior knowledge and digital literacy to learning motivation. The researcher took a quantitative research method with a correlational approach, sampling using stratified random sampling, so that 159 students were obtained for the sample. Based on the results of the study, it shows that interest in learning and motivation are interrelated with a magnitude of 0.438, prior knowledge to motivation is interrelated with a magnitude of 0.542, digital literacy to motivation is interrelated with a magnitude of 0.505 and interest in learning, prior knowledge and digital literacy to motivation are interrelated with a magnitude of 0.636. The conclusion of this study is the relationship between interest in learning and motivation is moderately correlated, the relationship between initial knowledge to learning motivation is moderately correlated, the relationship between digital literacy to learning motivation is moderately correlated, and the relationship between interest in learning, prior knowledge and digital literacy to learning motivation is strongly correlated.